Cultural Communication through Gambuh Dance : A Historical Performing Art from Bali - Suhendra, Eka Ari (Bali Tourism Board, 2023)
One of the most important factors driving artists to engage in the performing arts is the environment: artistic traditions within the family and the local community. In connection to the environment, there are three reasons why artists get involved in the arts: being appointed or requested, sometimes even 'forced' by the community, encouragement or a family calling, and personal willingness. Regarding the life and development of Gambuh and its instruments, it significantly influences other gamelan devices in terms of instrument usage, beat arrangement, song structure, motifs, and the names of some songs for various gamelan devices and specific types of compositions such as Semar Pegulingan, Pelegongan, Bebarongan, Joged Pingitan, Gong Gede, and Kebyar. In this study, a semiotic approach is used to analyze the elements of Gambuh Bali dance and reveal the messages contained within. First and foremost, in the semiotic study of Gambuh Bali, body movements become the primary focus. These movements can be seen as visual signs that carry implied meanings. Through the analysis of movements, messages related to character, emotions, and narratives in the dance can be uncovered. In the semiotic study of Gambuh Bali dance, the singing or chanting performed by the dancers can also be an object of analysis. Chants in Gambuh Bali dance play a crucial role in conveying cultural messages and expressing emotional nuances in the dance. By employing a semiotic approach, theoretical studies of Gambuh Bali dance can provide richer insights into the symbolism, cultural meanings, and messages embedded in this dance.